Enfoque familiar sobre cese de convivencia en la jurisprudencia del Tribunal Supremo Popular de Cuba (2019)
The concept of Home has different cultural meanings and subjective appropriations in family life. Conflicts associated with people’s permanence in a household contrast with the principle of family as the fundamental nucleus of society. In Cuba, whoever owns the property may declare the cessation of cohabitation to certain people. In case of nonconformity, either party may begin a trial that may end in the Supreme People’s Court. This highest judicial authority has developed extensive case law on this matter, since it is one of the most frequent lawsuits in the country. However, the family approach to this problem in sentences has been characterized by tenuous pronouncements. Currently, the Supreme People’s Court should balance family and owner interests, while establishing a separate family jurisdiction in Cuba.